On the travelling wave solutions of Ostrovsky equation - Demiray, Seyma Tuluce; Bulut, Hasan (Univ Tabriz, 2020)
In this paper, extended trial equation method (ETEM) is applied to find exact solutions of (1+1) dimensional nonlinear Ostrovsky equation. We constitute some exact solutions such as soliton solutions, rational, Jacobi elliptic and hyperbolic function solutions of this equation via ETEM. Then, we submit the results obtained by using this method.
Keywords: (1+1) dimensional nonlinear Ostrovsky equation; Extended trial equation method; Soliton solutions; Rational; Jacobi elliptic and hyperbolic function solutions